ANALISIS LITERASI MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL ALJABAR BERORIENTASI AKM NUMERASI DITINJAU DARI GAYA KOGNITIF - Rosiatul Qolbiyah; Christina Kartika Sari (Universitas Bhinneka PGRI, 2024)
The aims in this research is to identify the mathematical literacy skill of student based on cognitive style, specifically field independent (FI) and field dependent (FD), in solving AKM numeracy oriented problems in algebra content on SPLDV material. Descriptive qualitative are applied as the method with data collected through written test, interview, and documentation, validated using triangulation technique. The study use three main stages in data analysis: reducing data, presenting data, and make conclusion. The findings show that field independent student excel in various mathematical literacy indicator compared to field dependent students, including communications skill, devising strategies for solving problems, reasoning and argument, using symbolic, operations, technical language and formal language. However, field independent student still face challenges in mathematization and representation, especially in non-routine problems. Meanwhile, field dependent student have advantages in mathematical literacy indicators such as communications skill, reasoning and argument, using symbolic, operations technical language and formal language, thus requiring more assistance and explanations to achieve the same result as field independent students.